ADJACENT LEVEL DEGENERATION AND POST-TRAUMATIC DEFORMITY AFTER THORACOLUMBAR FRACTURES - SEBBEN,ANDRÉ LUÍS (2017)
ABSTRACT Objectives: To evaluate thoracolumbar fractures and the complications such as adjacent disc degeneration (ADD) and post-traumatic deformity. Methods: We evaluated 32 patients divided into two equal groups, 16 in the case group (removal of the synthesis material) and 16 in the control group (not submitted to removal of the synthesis material) in order to verify if there was difference between the incidence of these complications. Results: There were no statistically significant differences between the groups regarding the progression of the ADD and the post-traumatic deformity, but both progressed during the 2-year follow-up. Conclusion: It was concluded that the removal of the synthesis material was not effective in preventing these complications after surgical fractures of the thoracolumbar spine.